A RARE CASE OF ECTOPIC GIANT PROLACTINOMA MIMICKING CLIVAL CHORDOMA - Teh, Kai Xuan; Tee, Hwee Ching; Ho, Jin Hui (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Ectopic pituitary adenomas are extremely rare tumours which develop outside the sella turcica. The most common locations are the sphenoid sinus, clivus, suprasellar space, nasopharynx and cavernous sinus. Due to their rarity, these tumours are frequently misdiagnosed as other skull lesions such as chordoma, chondrosarcoma, meningioma or astrocytoma. We present a case of ectopic giant prolactinoma mimicking as clival chordoma. CASE A 38-year-old nulliparous female presented with oligomenorrhoea since the age of 20 and secondary amenorrhea at the age of 38 associated with galactorrhoea. Otherwise, she denied headache, symptoms of increased ICP or blurring of vision. There were no other symptoms to suggest pituitary hyper- or hypofunction. Her initial hormonal work-up showed hyperprolactinemia (>8000 ng/mL) with hypogonadotropic hypogonadism. MRI of the brain was signed out as clival chordoma measuring 2.3 x 3.6 x 4.1 cm displacing the pituitary gland and infundibulum. She underwent a biopsy of the lesion and the HPE confirmed pituitary lactotroph adenoma. She was started on cabergoline and her prolactin levels reduced significantly. CONCLUSION Ectopic pituitary adenomas occurring in the clivus are very rare. The main differential diagnosis to be considered is chordoma. Other than radiological imaging, additional endocrinological workup may be useful as well to establish the diagnosis. Biopsy of the lesion should be performed whenever the diagnosis is in doubt, as medical treatment with cabergoline often yields favourable outcomes in cases of ectopic prolactinoma which leads to a reduction in tumour size and prolactin level.